Challenges in Implementing the Merdeka Belajar Kampus Merdeka in Higher Education - Sihombing, Humiras Betty Marlina; Panjaitan, Jelita (Future Science / FSH-PH Publications, 2023)
Curriculum changes are a must. In fact, the very fast development of science and technology no longer supports the world of education to linger with the